Catalyzing urea hydrolysis using two-step microbial-induced carbonate precipitation for copper immobilization: Perspective of pH regulation - Xue, Zhong-Fei; Cheng, Wen-Chieh; Wang, Lin; Xie, Yi-Xin (Frontiers in Microbiology, 2022)
Microbial induced carbonate precipitation (MICP) has recently applied to immobilize heavy metals toward preventing their threats to public health and sustainable development of surrounding environments. However, for copper metallurgy activities higher copper ion concentrations cause the ureolytic bacteria to lose their activity, leading to some difficulty in forming carbonate precipitation for copper immobilization (referred to also as “biomineralization”). A series test tube experiments were conducted in the present work to investigate the effects of bacterial inoculation and pH conditions on the copper immobilization efficiency. The numerical simulations mainly aimed to compare with the experimental results to verify its applicability. The copper immobilization efficiency was attained through azurite precipitation under pH in a 4–6 range, while due to Cu2+ migration and diffusion, it reduced to zero under pH below 4. In case pH fell within a 7–9 range, the immobilization efficiency was attained via malachite precipitation. The copper-ammonia complexes formation reduced the immobilization efficiency to zero. The reductions were attributed either to the low degree of urea hydrolysis or to inappropriate pH conditions. The findings shed light on the necessity of securing the urease activity and modifying pH conditions using the two-step biomineralization approach while applying the MICP technology to remedy copper-rich water bodies.